Fenomenologia - Moryń, Mariusz (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
Phenomenology was founded by Edmund Husserl and developed by the followers like Max Scheler. It is the most important philosophical system of the 20th Century. Phenomenology, in Husserl’s conception, is primarily concerned with the systematic reflection and analysis of the structures of consciousness and the phenomena that appear in acts of consciousness. In its basic form phenomenology is the method of describing of the reality devoid of any assumptions and in consequence the key concepts in Husserl’s theory are notion of the pure consciousness and theory of transcendental phenomenology. Phenomenology thus attempts to create conditions for the objective study of topics usually regarded as subjective that is: consciousness and the content of conscious experiences such as judgements, perceptions and emotions.